CHANGE IN THE LEVEL OF CORPORATE LENDING IN POLAND DURING THE COVID-19 PANDEMIC - Mateusz Śliwa; Aleksandra Kłosowska (Polityki Europejskie, Finanse i Marketing)
The main theme undertaken in this paper is the assessment of the impact of the COVID-19 pandemic on corporate lending. The main objective of the article is to analyze the qualitative and quantitative changes in the level of corporate lending in Poland. The author focuses, on the one hand, on the ability of firms to incur liabilities and, on the other hand, on the changes in bank lending rules over the course of a changing economic reality burdened by the crisis caused by the pandemic. The individual analyses also show a broader comparative context by referring to statistical data before the onset of the virus crisis. In the case under review, uncertainty about the health of the MSP sector during the crisis weighed on the tightening of credit policy. An increase in demand for bank financing in the pandemic period was reported by both large companies and micro enterprises. However, only in the case of the former did the availability of loans increase. As a result, the gap between the availability of bank loans to large firms and the MSP sector widened.